Performa Broiler yang Dipelihara Pada Lantai Atas dan Lantai Bawah Kandang Postal Double Deck dengan Sistem Close House - Sultan, Sri; Horhoruw, Wiesje M; Wattiheluw, Muhammad J (Universitas Pattimura, 2023)
This study aimed to determine the performance of broilers kept on the upper and lower floors of double-deck postal cages with a semi-close house system. This research was conducted for 42 days consisting of 10 days of cage preparation and 32 days of data collection. The material for this study was broilers with the final Cobb strain CP-707 stock, with a population of 16,000 birds (8,000 birds/floor). Survey and observation methods are used to collect data related to broiler performance. The variables observed in this study were depletion, feed intake, body weight gain, feed conversion ratio (FCR), and performance index (IP). The data obtained were analyzed descriptively. The results show that based on the performance index, the performance of broilers kept in double-deck postal cages on the top floor is very good, and the bottom floor is good. Broilers on the upper floor have a higher performance index value than the lower floor due to lower depletion values, lower feed consumption with lower feed conversion values, and higher body weight.